Too big to jail? Uma análise longitudinal sobre o processo de identidade organizacional ameaçada - Ribeiro, Izabely Gibelato Santos (2022)
When the meanings that support the answers to the question "who are we as an organization" are challenged, individuals tend to face the phenomenon of Organizational Identity Threats. When diving into research on this phenomenon, we are faced with a complex dynamic, permeated by multiple interpretive layers and, according to the literature, many of these crossings are still unknown. Theoretical concerns about the experience of threats that lead organizational members to question who they are have been presented as if this experience occurred in a linear way, in subsequent stages marked by three main phases: i) recognition of the threat process; ii) elaboration of responses and, finally, iii) outcomes. In this research, I challenge this temporally delimited way of understanding the phenomenon to assume the theoretical lens of organizational identity threat to elaborate a longitudinal study on the crisis installed in a renowned construction company that faced a corruption scandal. By following this experience for five years, I was able to dive into the stories told by some of the executives who were at the forefront of organizational decisions taken in the face of the crisis that settled in the identity of that organization. By developing this study, I was able to reveal the subtleties that marked and unite each of the stages experienced in a global process. As a central contribution of this study, I present empirical evidence analyzed in the light of a theoretical model to support the argument about the power of understanding the stages that make up the process of threatened organizational identity, considering an analysis that crosses time and reveals the nuances that resonate in each one of those moments. As a methodological path, I assumed the thematic analysis of narratives and took into account the interpretations shared by 34 workers. The stories generously shared in this study were collected over the years the organization faced the corruption investigation process. In all, 64 formal interviews were carried out, observations were made at the organization's headquarters, in addition to a document analysis.